Soybean in rotation with cereals attenuates nitrous oxide emissions as compared with soybean monoculture in the Pampas region - Piccinetti, Carlos Fabian (2021)
Nitrous oxide (N-N2O) emissions in the agricultural sector represent ca. 25% of total N-N2O emissions on a global scale. In Argentina, information on agricultural emissions is scarce, and thus, N-N2O emissions are estimated by IPCC equations. Most reports in Argentina have estimated N-N2O emissions at crop scale, while few studies estimated emissions at the cropping system scale. Soybean in Argentina is mainly planted as monoculture, though, the inclusion of cereals in crop rotations may modify soil properties associated with N-N2O emissions such as water-filled pore space (%WFPS), soil temperature, or nitrate content. The objectives of this work were to: i) compare N-N2O emissions in crop sequences that include soybean in different proportions; ii) evaluate the impact of these emissions in relation with N inputs (fertilizer + BNF) at the cropping sequence level, and iii) compare these observations with emissions as estimated by the IPCC equation (tier 1). During two years, N-N2O emissions, soil N-NO3-, soil WFPS, and soil temperature were measured biweekly in a long-term experiment under no-tillage in four sequences: i) full-season soybean monoculture (S-S); ii) winter cover crop/soybean (CC/S); iii) double-cropped wheat/soybean -- maize (W/S-M), and vi) double-cropped wheat/soybean -- winter cover crop/maize (W/S-CC/M). Aboveground biomass, yield (expressed in glucose equivalents), and nitrogen (N) uptake were determined for each crop at harvest. For soybean, additionally to these variables, N derived from biological N fixation (BNF) was determined, as well. N-N2O emissions were scaled to yield and to vegetative biomass. During the two years of this study, cumulated biomass (expressed in glucose equivalents) was significantly lower in S-S and CC/S (29.5 and 36.8 Mg GluEq ha−1, respectively) than in W/S-M and W/S-CC/M (48.6 and 54.6 Mg GluEq ha−1, respectively). In the same period, exported cumulated N with grains was similar among sequences averaging 277 kg N ha−1, while the largest cumulated N input (N fertilizer + BNF) was 392 kg N ha−1 in W/S-CC/M, surpassing the other sequences by 100%. N-N2O flux rates were the lowest in W/S-M (7.8 μg N-N2O m-2h−1) and the highest in CC/S (19.0 μg N-N2O m-2h−1). Therefore, at the cropping sequence level, N-N2O emissions represented on average 0.62% of cumulated N inputs. A multiple regression model indicated that N-N2O emissions were more related to soil %WFPS (0–20 cm) and soil temperature (at 10 cm). IPCC direct emission equation (tier 1) overestimated N-N2O emissions for W/S-M and W/S-CC-M. In absolute terms, sequences including cereals showed similar cumulated emissions to S-S, however, when emission were scaled to unit yield or vegetative biomass, sequences that included cereals in the rotation attenuated N-N2O losses.